STATE’S FISCAL POLICY IN TERMS OF A CRISIS - Julia V. Trushina (Статистика и экономика, 2016)
A package of measures of anti-crisis fiscal regulation in Russia and its impact on the current situation of fiscal area of Russian are considered in the article. The measures taken by Government in the sphere of taxation in the 2008-2009 are presented.